Mezinárodní trestní soud a jeho předchůdci (Czech Journal of International Relations, 2000)
Fifty years after the Nuremberg and Tokyo trials, the international community entered the final stage of work on the establishment of a permanent International Criminal Court ( ICC). The primary aim of the Court would be to bring to justice persons responsible for the most serious crimes under international law, when domestic criminal justice systems fail to do so. The ICC would act as a standard-setting institution in the area of fair trial and due process standards, and serve as a model of international justice.The jurisdiction of the independent, effective and fair ICC should initially be limited to three core crimes: genocide, war crimes and crimes against humanity. All three crimes constitute exceptionally serious crimes of concern to the international community as a whole and are well established as crimes under customary international law.The ICC Statute defines genocide pursuant to the definition provided for in the 1948 Genocide Convention, which has been ratified by many states and is widely accepted as reflecting customary international law. Acts of genocide may be committed in peacetime as well as in armed conflict.War crimes included in the ICC Statute cover acts committed both in international and non-interactional armed conflict. The enumeration of crimes committed in international armed conflict corresponds to the grave breaches of the 1949 Geneva Conventions, the grave breaches and denials of fundamental guarantees of Additional Protocol I to Geneva Conventions, and violations of the 1907 Hague Convention IV and its Regulations, and crimes committed in non-international armed conflict, provided for in Common Article 3 of the Geneva Conventions and Additional Protocol II to Geneva Conventions.The ICC Statute defines crimes against humanity as acts committed on a widespread or systematic basis against a civilian population. The enumeration of such crimes should include: murder, extermination, enslavement, deportation, arbitrary detention, torture, extrajudicial executions, forced disappearance of persons, rape, forcible transfers of populations within or across national borders, persecution on political, ethnic, racial, religious and other grounds and other inhumane acts. Crimes can be committed both in time of peace and in armed conflict, by official and non-state actors.